ANALYSIS OF ENVIRONMENTAL SANITATION AND COMMUNITY LIVES IN SMALL ISLANDS BY INDEX INSTRUMENT DEVELOPMENT (CASE STUDY: PANGGANG ISLAND, KEPULAUAN SERIBU DISTRICT) - Mary Nayuki, Catherine
The phenomenon of poor sanitation and slum settlements can be seen on small islands designated as residential islands. Small islands require special attention according to their characteristics and designations. Proper environmental management requires a comprehensive and systemic analysis of the components of small island. Many environmental assessment instruments have been developed, but the unique characteristics of small islands require further study and research to assess sanitation and community lives. Instruments for the assessment of environmental sanitation systemically and comprehensively in specific areas such as small islands have not existed until now. For this reason, this index was developed to meet the needs of assessment instruments that can provide a comprehensive picture of actual conditions. This study aims to develop an index instrument for environmental sanitation and community life in small islands by involving components of water quality, community welfare, and potential biological resources. Case study conducted in Panggang Island. The research location is in Sub-District of North Kepulauan Seribu, Kepulauan Seribu District, DKI Jakarta. This island is the most populous residential island in the Kepulauan Seribu cluster with the phenomenon of poor sanitation. The method used is the development of multiple criteria that begins with compiling a viewpoint on environmental problems in densely populated small islands. The next step is to create the Environmental Sanitation Index Instrument for small islands by developing a multiple criteria method adopted from the Multi-Criteria Decision Analysis (MCDA). The development of multi-criteria method is done by determining the level of interest indicators, weighting, calculation of composite components and indicators. The determination of the level of importance of indicators is carried out by making a questionnaire instrument that will be used to collect interview data using the Delphi method, a method that involves The Experts. Data obtained from the interviews were processed to determine the value of the indicators that will be used in the making of the Small Islands Environmental Sanitation Index. This index is used as an instrument for assessing the criteria of each component related to the research objectives, which is the analysis of sanitation in small islands. Then the spatial analysis is carried out based on the index value. The results showed the index value was 52.40. This shows that environmental sanitation and community lives are in moderate status. This value is consistent with the situation in the study area that most people have adequate sanitation facilities derived from subsidies, but are unable to apply sanitation principles due to low education and welfare. The index results show that environmental pollution occurs in amounts that can harm health, water quality is below standard, and environmental awareness is quite low. The application of the developed index to the data from the study area shows that the indicators in each component are suitable for assessment and sufficiently provide comprehensive criteria. Indicators in the groundwater quality component are suitable for assessment, because groundwater as a source of water in densely populated small islands tends to experience pollution problems due to sea water intrusion and household activities. The indicators in the community welfare component are also quite suitable for assessment. This component is able to describe the ability of communities in small islands to implement sanitation practices, because inadequate sanitation practices are the impact of low community welfare. The component of marine biological resource potential is also suitable for assessment because it can quantify the state of marine biological resources, and assess environmental awareness based on fishermen's knowledge of the preservation of marine biological resources. The validity of this index is limited to the validity of the criteria used. This index is expected to become an environmental sanitation assessment instrument that can be applied to other small islands which have similar characteristics with the study area.